Physical Condition Relationship With Independence Elderly At Home Social Protection Tresna Werdha Garut - hasbi Taobah Ramdani (STIKes Karsa Husada Garut, 2015)
This research is motivated by the increasing success of the government in the various aspects of national development so that life expectancy increased the so growing population. After observation in Social Protection Home Tresna Werdha Garut are elderly people who need help in doing the fulfillment of physical activity. Therefore we need research on the physical state of the independence of the elderly. Descriptive study of correlation in this study aims to determine the relationship between the physical state of the independence of the elderly in the Social Protection Home Tresna Werdha Garut. This study was conducted on 67 respondents with a total sampling technique. Data were collected using a questionnaire for self-reliance and the Barthel Index vitalsign examination to obtain the elderly physical state data is then performed data analysis using Spearman Rank Correlation calculations. The results of this study indicate that the majority of respondents (73.1%) independent of activity, and majority of the respondents (76.1%) with a healthy physical state. While the bivariate analysis between the physical state and the independence of the elderly showed a correlation with the value of correlation (r) 0.291 (r> 0.2369) and the p-value of 0.016 (p <0.05). The conclusion of this study is a significant correlation between the physical state of the independence of the elderly in the Social Protection Home Tresna Werdha Garut. The better the physical state of the elderly will increase the independence of the elderly. Therefore it is necessary for the inspection and maintenance of the physical condition of the elderly is continued and sustained to increase the independence of the elderly